2017
DOI: 10.1038/s41598-017-14667-4
|View full text |Cite
|
Sign up to set email alerts
|

sRAGE alleviates neutrophilic asthma by blocking HMGB1/RAGE signalling in airway dendritic cells

Abstract: Receptor for advanced glycation end products (RAGE) plays a role in inflammatory reactions. The soluble form of RAGE (sRAGE) acts as a decoy to inhibit interactions of RAGE with advanced glycation end products such as High mobility group box 1 (HMGB1). We have demonstrated that HMGB1 directs Th17 skewing by regulating dendritic cell (DC) functions in a previous study. However, the protective effects of HMGB1 blockade with sRAGE in the development of neutrophilic asthma remain unclear. Here, we showed that alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…HMGB1 can recruit and activate DCs and instruct DCs to trigger T H 2 responses following HDM sensitization. 4,24,32 Thus, the elevated levels of extracellular HMGB1 after HDM exposure in Pag1 −/− mice may be responsible for the increased recruitment of MoDCs to the lung and mLNs. As an innate source of type 2 cytokines, ILC2s also facilitate the differentiation of CD4 + T cells to T H 2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 can recruit and activate DCs and instruct DCs to trigger T H 2 responses following HDM sensitization. 4,24,32 Thus, the elevated levels of extracellular HMGB1 after HDM exposure in Pag1 −/− mice may be responsible for the increased recruitment of MoDCs to the lung and mLNs. As an innate source of type 2 cytokines, ILC2s also facilitate the differentiation of CD4 + T cells to T H 2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…AAV9 is widely used in the research of respiratory for it is one of the most e cient serotypes to infect lung epithelium cells. Studies have reported that sRAGE reduced the neutrophil in ltration of lung tissue in LPS-induced acute lung injury mouse model [15] and the airway neutrophil in ammation in asthmatic mice [16]. Consistent with the existing research, overexpressed sRAGE not only signi cantly reduced the in ltration of in ammatory cells and in ammation score of lung tissue in NA mice but also sharply inhibited the in ammatory cells and neutrophils in BALF, which implying that sRAGE de ciency may participate in airway neutrophilic in ammation of NA mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, AAV9-sRAGE restored the expressions of E-cadherin and Vimentin, implying that sRAGE overexpression may reduce airway EMT in NA mice. A study has revealed that sRAGE alleviated the Th17 cell response and airway neutrophilic in ammation in NA mice through competing with a RAGE ligand -HMGB1 [16]. RAGE was highly expressed in the lung tissues of asthmatic mice and was involved in the mucus hypersecretion and airway remodeling of asthma [31].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of RAGE with these ligands leads to activation of inflammatory responses, induction of oxidative stress and tissue remodeling responses. Soluble form of receptor for advanced glycation end‐products serves as a decoy receptor by sequestering RAGE ligands and thus inhibiting RAGE dependent cellular responses . However, further studies are needed to determine whether deficiency in sRAGE is a causative factor for airway neutrophilia or rather a result of neutrophilic inflammation (degradation due to excessive levels of neutrophil‐derived enzymes).…”
Section: Endotypes and Underlying Mechanisms Of Non‐t2 Asthmamentioning
confidence: 99%